Early report on brain arousal regulation in manic vs depressive episodes in bipolar disorder. (September 2016) - Wittekind, Dirk Alexander; Spada, Janek; Gross, Alexander; Hensch, Tilman; Jawinski, Philippe; Ulke, Christine; Sander, Christian; Hegerl, Ulrich
Abstract: Objectives: The arousal regulation model of affective disorders attributes an important role in the pathophysiology of affective disorders to dysregulation of brain arousal regulation. According to this model, sensation avoidance and withdrawal in depression and sensation seeking and hyperactivity in mania can be explained as auto‐regulatory attempts to counteract a tonically high (depression) or unstable (mania) arousal. The aim of this study was to compare brain arousal regulation between manic and depressive bipolar patients and healthy controls. We hypothesized that currently depressed patients with bipolar disorder show hyperstable arousal regulation, while currently manic patients show unstable arousal regulation. Methods: Twenty‐eight patients with bipolar disorder received a 15‐min resting electroencephalogram (EEG) during a depressive episode and 19 patients received the same during a manic/hypomanic episode. Twenty‐eight healthy control subjects were matched for age and sex. The Vigilance Algorithm Leipzig (VIGALL), which classifies 1‐s EEG segments as one of seven EEG‐vigilance substages, was used to measure brain arousal regulation. Results: Manic patients showed more unstable EEG‐vigilance regulation as compared to the control sample ( P = .004) and to patients with a depressive episode ( P ≤ .001). Depressive patients had significantly higher mean vigilance levels ( P = .045) than controls. Conclusions: A clear difference was found in the regulation of brain arousal of manic patients vs depressive patients and controls. These data suggest that brain arousal might depend on the current mood state, which would support the arousal regulation model of affective disorders.